Increasing Public Awareness in Compliance with Paying Vehicle Taxes through Behavioural Change Communication: A Case Study in Bekasi City - Krishantoro, Krishantoro; Ayu, Renisya; Susanti, Sri; Star, Yurisman (Technium Social Sciences Journal, 2022)
The largest source of state revenue comes from taxes. Taxes are people’s contributions to the state treasury for which there are no direct replies or rewards. One type of tax that has the potential to increase along with the development of technology and the community’s economy as well as the needs of the community is the motor vehicle tax. However, until now there are still many people who do not have the awareness to pay their vehicle tax. This, in addition to harming the owner of the vehicle, also affects regional income so that it can hinder the pace of development in various regions. This research is at answering the questions of what factors make the society do not have awareness for paying vehicle tax and how to implement the behavioural change communication to increase people’s awareness. This is a qualitative research with a case study approach. The data collection was carried out by semi-structured interviews with 10 community representatives with the objective is to find out how the Behavioural Change Communication is implemented in Bekasi City to increase people’s awareness in paying the vehicle tax. This study proves that the Behavioural Change Communication program can change people’s behaviour from those who were previously disobedient to paying taxes to someone who prioritises their finances for taxes.